Pharmacoeconomics of spastic cerebral palsy - R. I. Yagudina; A. U. Kulikov; N. I. Korolyova; D. T. Ugrekhelidze (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Cerebral palsy (CP) is one of the most widespread and socially significant neurological diseases that affect both various aspects of physical and psychoverbal development of children since birth and stages of their personal development and adaptation in society. Over the last years there has been an increase in the number of children with disabilities in Russia, and it should be noted that CP ranks first among neurological disabilities in children. Given the lifetime course of this disease, CP acquires a huge medical and socioeconomic relevance. In particular, it is necessary to use the most efficient medical technologies (from the point of view of both efficacy, safety and costs). Pharmacoeconomic analysis is the most suitable tool for solving these tasks. However, when performing pharmacoeconomic analysis in the field of cerebral palsy, as well as in any other disease area, it is obligatory to take into account certain peculiarities at the planning and implementation stages. The authors of the article have identified specific features of pharmacoeconomic analysis methods based on assessment of health technologies related to cerebral palsy.